2004
DOI: 10.5488/cmp.7.1.157
|View full text |Cite
|
Sign up to set email alerts
|

Polaron in Cylindrical and Spherical Quantum Dots

Abstract: Polaron states in cylindrical and spherical quantum dots with parabolic confinement potentials are investigated applying the Feynman variational principle. It is observed that for both kinds of quantum dots the polaron energy and mass increase with the increase of Fröhlich electron-phonon coupling constant and confinement frequency. In the case of a spherical quantum dot, the polaron energy for the strong coupling is found to be greater than that of a cylindrical quantum dot. The energy and mass are found to b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…The Feynman variational principle [29][30][31][32][33] is one of the most effective methods when investigating the polaron problem for arbitrary values of the electron-phonon coupling constant . The basis of Feynman variational method is the Jensen-Feynman inequality: 20…”
Section: Feynman Variational Principlementioning
confidence: 99%
“…The Feynman variational principle [29][30][31][32][33] is one of the most effective methods when investigating the polaron problem for arbitrary values of the electron-phonon coupling constant . The basis of Feynman variational method is the Jensen-Feynman inequality: 20…”
Section: Feynman Variational Principlementioning
confidence: 99%
“…The usual Fröhlich polaron Hamiltonian describing an electron confined in 2D and interacting with the optical phonon with a parabolic potential is [5] (1)…”
Section: Theorymentioning
confidence: 99%
“…Recent advances in microfabrication techniques have made the fabrication of low-dimensional structures possible and have therefore, tend to a great of work on the effect of the electron-phonon interaction in reduced dimensionality [1][2][3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…They conclude that with the increase in the dot radius the magnitude of the polaron energy shift decreases rapidly from large value and then approaches gradually to the bulk value. Fai et al 5 researched the polaron in cylindrical and spherical QDs with parabolic confinement potentials by applying the Feynman variational principle. It is shown that in the case of a spherical QD, the polaron energy for the strong coupling is found to be greater than that of a cylindrical QD.…”
Section: Introductionmentioning
confidence: 99%